2008
DOI: 10.1099/mic.0.2008/016923-0
|View full text |Cite
|
Sign up to set email alerts
|

A role for tumour necrosis factor-α, complement C5 and interleukin-6 in the initiation and development of the mycobacterial cord factor trehalose 6,6′-dimycolate induced granulomatous response

Abstract: A role for tumour necrosis factor-a, complement C5 and interleukin-6 in the initiation and development of the mycobacterial cord factor trehalose 6,69-dimycolate induced granulomatous response

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 55 publications
10
69
0
Order By: Relevance
“…Additionaly, its purity was confirmed by two-dimensional TLC as described above for the cord factors from M. alvei and M. brumae. This commercial glycolipid has been used by several authors (Indrigo et al, 2003;Welsh et al, 2008), and similar results to those of the cord factor purified in the laboratory of the authors have been obtained by Dao et al (2008). ) in deuterochloroform/deuteromethanol (6 : 1, v/v).…”
Section: Methodssupporting
confidence: 52%
See 2 more Smart Citations
“…Additionaly, its purity was confirmed by two-dimensional TLC as described above for the cord factors from M. alvei and M. brumae. This commercial glycolipid has been used by several authors (Indrigo et al, 2003;Welsh et al, 2008), and similar results to those of the cord factor purified in the laboratory of the authors have been obtained by Dao et al (2008). ) in deuterochloroform/deuteromethanol (6 : 1, v/v).…”
Section: Methodssupporting
confidence: 52%
“…Briefly, IL-12p40 favours the Th1 response and the resistance to mycobacterial infections (Cooper & Khader, 2008), but the role of IL-6 is controversial. In some experiments, IL-6 appeared as a pathological cytokine, helping to maintain the granuloma (Welsh et al, 2008), and in others it participated in the differentiation of Th17 cells (cited by Méndez-Samperio, 2010), a subset of T cells that secrete IL-17. TNF-a is, among other functions, critical for the initiation of the granuloma (Russell, 2007), and IL-1b has a role in both innate and adaptative immunity (Korbel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TNF -/-mice or the IL-6 -/-mice demonstrated that TNF is critical for initiation of the granulomatous response, and IL-6 plays a key role in the granuloma maintenance response (Welsh et al, 2008). Unlike Il-6 -/-mice, TCZ does not completely inactivate the IL-6 system because TCZ works as a competitive inhibitor of IL-6.…”
Section: Mycobacterium Infectionmentioning
confidence: 99%
“…Microspheres coated with TDM showed an increased expression of enzymes and matrix metalloproteinases; molecules associated with tissue remodeling and tissue destruction during caseating granulomas [31]. The inflammatory profile induced by TDM has been related with granuloma development and maintenance, this phenomenon is related with TDM, and is dependent of TNF-α and IL6 expression; also C5a complement factor has been described as part of the granuloma maintenance microenvironment molecule [32].…”
Section: Trehalose-66´-dimycolate (Tdm)mentioning
confidence: 99%